2014
DOI: 10.7341/20141034
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Locally Embedded Personal Relationships for SME Internationalisation Processes – from Opportunity Recognition to Company Growth

Abstract: The purpose of the paper is to present the importance of locally embedded personal relationships and individuals '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…Having domestic partners with international experience enables SMEs to gain a better understanding of how to conduct international business, ultimately boosting the confidence of ventures in the context of internationalizing by mitigating process-related uncertainty or lowering the perceived cost of serving foreign markets in general [Milanov and Fernhaber, 2014]. Ratajczak-Mrozek [2014] points out that local personal networks promote SMEs' internationalization process and growth. Embeddedness in local personal networks is conducive to recognizing the potential for SMEs to internationalize and to plan its implementation.…”
Section: Domestic Vs Foreign Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Having domestic partners with international experience enables SMEs to gain a better understanding of how to conduct international business, ultimately boosting the confidence of ventures in the context of internationalizing by mitigating process-related uncertainty or lowering the perceived cost of serving foreign markets in general [Milanov and Fernhaber, 2014]. Ratajczak-Mrozek [2014] points out that local personal networks promote SMEs' internationalization process and growth. Embeddedness in local personal networks is conducive to recognizing the potential for SMEs to internationalize and to plan its implementation.…”
Section: Domestic Vs Foreign Networkmentioning
confidence: 99%
“…Previous empirical studies on networking show the importance of networks in many different processes, such as internationalization (e.g., Danik and Kowalik, 2015) or innovation (e.g., Sarwar et al, 2021), but comparative studies can hardly be found (exceptions include the study of Chang and Webster [2019], who have shown that access to the professional networks of Australian SMEs increases the probability of exporting). Moreover, the international business research discusses mainly the importance of foreign networks, while only some authors (e.g., Boehe, 2013;Milanov and Fernhaber, 2014;Ratajczak-Mrozek, 2014;Zahoor and Al-Tabbaa, 2021) concentrate on the local ones. We do not know which networks contribute more to a company's success and whether internationally operating companies differ from locally oriented ones in their ability to take greater advantage of their network.…”
Section: Introductionmentioning
confidence: 99%
“…sharing the same values, hobbies, etc. However, as the emergence of a relationship with emotional background is usually very timeconsuming (Bachman, 2001), one can assume that it is created only if the business relationship has also strong objective rationale (Movery, Oxley & Silverman, 1998;Czakon, 2011;Ratajczak-Mrozek, 2014). A longer cooperation gives a chance to support cognitive and affective levels of trust upon mutual assessment of behavior in terms of predictability, reliability, authenticity, communication accessibility and moral values (Mathers, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis of the studies of two cases carried out by Ratajczak and Mrozek (2014) has shown that the main factors affecting the ratio of personal relationship on the emergence of opportunity associated with the possibility of internationalization are trust and mutual understanding. At the same time, the author stresses that as these relationships help create opportunities, for their realisation and the relation on the internationalisation and the growth of company, you need additional identified social factors (entrepreneurial attitude) and economic factors (quality and competitive prices).…”
Section: The Importance Of the Relationship Of Managers With Subordinmentioning
confidence: 99%